2009
DOI: 10.1080/02614360903078659
|View full text |Cite
|
Sign up to set email alerts
|

Identity work: young disabled people, family and sport

Abstract: It has long been recognised that family is an important arena in which sporting tastes and interests are nurtured. Indeed, for many young people the family introduces them to and then provides ongoing support for engaging in sport. Research has also indicated that the family has a significant position in the lives of young disabled people. In this paper we explore the interrelationships between sport, family and disability. Like a number of writers within disability studies we see the benefits of moving beyond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 46 publications
1
33
0
1
Order By: Relevance
“…In many such cases, few adjustments are made to provision and the school system essentially remains unchanged (Fitzgerald, 2012). Indeed, several researchers suggest that 'mainstream' experiences can be isolating and evoke feelings of exclusion (Fitzgerald, 2005;Fitzgerald & Kirk, 2009;Goodwin & Fitzgerald, 2009). Consequently, the importance of examining the processual characteristics of inclusion, as well as understanding this process from stakeholder and student perspectives, has been highlighted (Slee, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In many such cases, few adjustments are made to provision and the school system essentially remains unchanged (Fitzgerald, 2012). Indeed, several researchers suggest that 'mainstream' experiences can be isolating and evoke feelings of exclusion (Fitzgerald, 2005;Fitzgerald & Kirk, 2009;Goodwin & Fitzgerald, 2009). Consequently, the importance of examining the processual characteristics of inclusion, as well as understanding this process from stakeholder and student perspectives, has been highlighted (Slee, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Las teorías sobre convivencia se apoyan en la interiorización de los valores, y en la autorregulación de conductas (Campo, Fernández y Grisaleña, 2005), así como, en la competencia social y emocional (Ayestaran, 1999). Se entiende por competencia social la capacidad para manejar las emociones, para resolver los conflictos de la vida, controlando los impulsos y colaborando con otras personas (Fitzgerald y Kirk, 2009, Prat y Soler, 2003.…”
Section: Introductionunclassified
“…That certain social agents such the family, the media and the school with its teachers and monitors exert a great influence on educating children about values. So it was that, on the basis of a number of working initiatives and campaigns with families [12,17], we began this process of education and awareness among families through a number of research projects. The Basque Government's sport violence committee has found that one of the main causes of violence in sport is rooted in school sport.…”
Section: From Our Conception Of School Sport To Participational Constmentioning
confidence: 99%
“…These competitive activities should serve to encourage positive values [12,3] and that competitions and their context should be conceived to give all the participants a reasonable chance of succeeding, in such a way as to enable them to overcome personal barriers. In the search for performance: There is a tendency to enhance the feelings of competence and incompetence with respect to physical activities.…”
Section: From Our Conception Of School Sport To Participational Constmentioning
confidence: 99%
See 1 more Smart Citation